The effects of elastic band resistance training on serum levels of growth differentiation factor 11, myostatin, and insulin resistance in overweight elderly women - Akbar Azamian Jazi; Elias Abdellah (Shahid Beheshti University, 2024)
Background and Purpose: Growth differentiation factor 11 (GDF11) and myostatin (growth differentiation factor 8) are related to most diseases and chronic disorders in elderly population. Even though these two factors have similar structural and signaling pathways, they can have different functions, and the available information about their effects on the regeneration of degenerated muscles during old age is contradictory. GDF11 plays a role in skeletal muscle regeneration, combating aging-induced muscle loss, and regulating metabolic homeostasis and energy balance. On the other hand, myostatin, mainly secreted by skeletal muscles, plays a role in inhibiting muscle hypertrophic response (negative regulation of muscle mass) and modulating metabolic processes. Also, its increased expression is related to obesity and insulin resistance. Considering the beneficial effect of resistance training on these variables, the present study aimed to investigate the effect of 12 weeks of elastic band resistance training on the serum levels of growth differentiation factor 11, myostatin, and insulin resistance in overweight elderly women.Materials and Methods: Twenty-eight overweight elderly women with an average age of 74.04 ± 4.69 years and a body mass index of 28.21 ± 3.35 kg/m2 were selected based on the inclusion criteria and then randomly divided into exercise (n = 14) and control (n = 14) groups. Subjects in training group performed 12 weeks of Elastic band resistance training, 3 days per week. Blood samples were taken 24 hours before the first training session and 48 hours after the last training session; and were analyzed for serum levels of GDF11, myostatin, insulin, and glucose. All data were analyzed by two-way repeated-measures of ANOVA and using SPSS version 25 software at a significance level of P<0.05.               Results: After 12 weeks of elastic band resistance training, there were no significant differences in GDF11, BMI, and WHR variables between the two training and control groups (p>0.05), though, the serum levels of myostatin (P=0.027), insulin resistance index (P=0.045) and body fat percentage (P=0.023) decreased significantly.Conclusion: It seems that the decrease in the level of myostatin following elastic band training, which was associated with a reduction in insulin resistance and body fat percentage, can have a positive effect on the muscle mass and energy homeostasis of overweight elderly women. Also, in future studies related to GDF11, it is necessary to select the type, duration, and intensity of exercise as well as measurement methods with more scrutiny and accuracy.